Keefektifan Dosis Koagulan Poly Aluminium Chloride (PAC) Dalam Menurunkan Kadar Total Suspended Solid (TSS) Air Limbah Laundry - Kartika, Riza Yuni, Dwi Astuti, SKM., M.Kes, Sri Darnoto S.KM M.PH (2015)
The degree of TSS substances in waste water which are higher than quality standard can create health, beauty and damage objects disruption. The degree of TSS substances in Sakura Laundry Jalan Mencoraya Gg. Menco XXXII, Nilasari Baru RT 10 RW 01, Gonilan Kartasura Sukoharjo is higher than quality standatd accepted 350 mg/l. The decrease of the degree of TSS can be conducted by coagulation, flokulation and sedimentation processing using coagulant PAC. The purpose of this research was to find the effectiveness of the coagulant doses PAC in decreasing the degree of TSS laundry waste water. The research used true experiment method applying the research design of pretest and posttest with control group. The population in this research was waste water in Sakura Laundry with the volume of waste water every day ±210 liters. Total sampel used in the research was 30 liters, each treatment needs 1 liters with three times repetition. Sampling technique with quota sampling. The statistics test used one way anova. The result of the statistict test shows that there was effectiveness of the coagulant doses PAC in decreasing the degree of TSS. The result of treatment with coagulant doses PAC 0,1 gr/l; 0,15 gr/l; 0,2 gr/l and 0,25 gr/l each an average of 33,33mg/l; 23,33 mg/l; 36,67 mg/l and 43,33 mg/l. The most effective of coagulant doses PAC in decreasing the degree of TSS laundry waste water was doses 0,15 gr/l with effectiveness of 93,27%.